The Role of Brand Ambassador and Electronic Word of Mouth towards Purchase Intention - Prasetio, Adhi; Purnamawati, Eko Dinar (JDM (Jurnal Dinamika Manajemen), 2023)
Beauty trends and Indonesian women are inseparable and make the cosmetic industry have the potential to continue to grow in the future. Recent media promotion trends show that Instagram is an essential medium for companies engaged in the cosmetic industry. The results of research conducted by the Zap Beauty Index in 2020 showed that as many as 77.2% of Indonesian women use social me- dia Instagram to find body care and beauty products. The purpose of this study is to analyze the role of brand ambassadors and three dimensions of eWOM: the eWOM quality, eWOM quantity, and the sender’s expertise in predicting purchase intention. This study is based on a survey of 400 online respondents. This research uses descriptive and SEM-PLS analysis techniques. Based on the study results, it can be concluded that brand ambassador, eWOM quality, eWOM quantity, and sender’s expertise have positive and significant influences in predicting purchase intention. As a managerial implication, our findings can help strategic marketing managers and marketers to focus on the identi- fied factors that drive purchase intention.